β1-Adrenoceptor Activation Is Required for Ethanol Enhancement of Lateral Paracapsular GABAergic Synapses in the Rat Basolateral Amygdala - Silberman, Yuval (The American Society for Pharmacology and Experimental Therapeutics, 2012)
Ethanol (EtOH) potentiation of GABAergic neurotransmission in the basolateral amygdala (BLA) may contribute to the acute anxiolytic effects of this drug. Previous studies have shown that BLA pyramidal neurons receive GABAergic input from two distinct sources: local interneurons and a cluster of GABAergic cells termed lateral paracapsular (LPCS) interneurons. It is noteworthy that whereas EtOH enhances local GABAergic synapses via a presynaptic increase in GABA release, EtOH potentiation of LPCS inhibition is mediated via a distinct mechanism that requires adrenoceptor (AR) activation. Here, we sought to further characterize the interaction between the AR system and EtOH enhancement of LPCS GABAergic synapses by using in vitro electrophysiology techniques in male Sprague-Dawley rats. Exogenous norepinephrine (NE) enhanced LPCS-evoked inhibitory postsynaptic currents (eIPSCs) via the activation of β-ARs, because this effect was blocked by propranolol. EtOH potentiation of LPCS eIPSCs was also blocked by propranolol and significantly reduced by NE pretreatment, suggesting that NE and EtOH may enhance LPCS inhibition via a common mechanism. EtOH enhancement of LPCS eIPSCs was significantly reduced by a selective β1-, but not β2- or β3-, AR antagonist, and both EtOH and NE potentiation of LPCS IPSCs was blocked by postsynaptic disruption of cAMP signaling. These data suggest that EtOH enhances LPCS synapses via a postsynaptic β1-AR, cAMP-dependent cascade. Because enhancement of LPCS inhibition can reduce anxiety-like behaviors, these findings shed light on a novel mechanism that may play a role in some of the anxiolytic effects of EtOH that are thought to contribute to the development and progression of alcoholism.